Participatory Action Research to Strengthen Community Early-Warning Facilitators in Nonformal Education: An Indonesian Case - Ninil Riyati Miftahul Jannah; Sujarwo Sujarwo; Gumpanat Boriboon (Universitas Negeri Semarang, 2026)
Background - Facilitator capacity is critical for the effectiveness of community-based early warning systems (CBEWS) in disaster risk reduction. Facilitators serve as intermediaries translating complex hazard data into actionable insights that enable communities to respond effectively to disasters. In Indonesia, where disaster risk is high, facilitators play an essential role in protecting lives and livelihoods at the grassroots level. Urgency of Research - Despite their importance, capacity-building approaches for CBEWS facilitators often employ top-down training methods that fail to engage facilitators as active agents in their own learning. Current programs lack participatory approaches that leverage facilitators' contextual knowledge and experience, undermining the sustainability and relevance of capacity-building initiatives. There is an urgent need for innovative, participatory approaches that position facilitators as co-creators of knowledge. Research Objectives - This study aimed to describe the process and outcomes of implementing participatory action research (PAR) to enhance the capacity of CBEWS program facilitators in nonformal education settings, investigating how PAR supports facilitator understanding of CBEWS concepts, develops contextual and adaptive facilitation skills, cultivates reflective capacity, and identifies enabling and inhibiting factors. Research Method - This qualitative descriptive study was conducted between 2021 and 2024 across seven disaster-prone Indonesian provinces: Central Java, East Java, West Java, Banten, South Kalimantan, Gorontalo, and Bali. Forty-five CBEWS facilitators participated in PAR cycles involving planning, action, observation, and reflection stages. Data were collected through 60+ hours of participatory observation, 20 in-depth interviews, 8 focus group discussions, and document analysis. Thematic analysis was employed to identify patterns and themes. Research Findings - Three dimensions of capacity development emerged: enhanced understanding of CBEWS concepts applicable to specific disaster contexts; improved contextual and adaptive facilitation skills enabling tailoring of approaches to community needs and creation of inclusive learning environments; and cultivated reflective capacity for systematic practice improvement. Enabling factors included institutional support, facilitator openness to learning, and collaborative researcher-facilitator relationships. Inhibiting factors included limited time for reflection, dual roles as implementers and learners, and organizational barriers. Research Conclusion & Novelty - Participatory action research effectively develops facilitator capacity when supported by institutional commitment and multi-year engagement. This approach provides a viable model for community-based disaster risk reduction programs, contributing to both adult learning theory in nonformal education settings and practical disaster risk reduction implementation.